Las Habilidades Informáticas en la Resolución de Problemas Matemáticos en los estudiantes del décimo año de la Unidad Educativa Miguel Ángel León - Cazorla Morales, Lady del Rocío (2017)
This research addressed the theme "Computer skills in solving mathematical problems in the students of the tenth year of the Unidad Educativa" Miguel Ángel León ". It is a topic of great importance since it allowed to determine the computer skills of the students of the tenth year of the Unidad Educativa “Miguel Angel Leon” in order to solve problems. The computer skills is more than just interacting with an educational software. It helps significantly in solving problems with more efficiency and agility. In reference to the methodology, it was a descriptive research. The type of research was field research. The level of research was diagnostic - exploratory. The population was composed of the students of the Unidad Educativa "Miguel Angel Leon". The sample consisted of 35 students from the tenth of the class "F" of General Basic Education. The technique used for the evaluation of the students was the questionnaire in order to verify if they use the TICS to solve problems. After performing the analysis and interpretation of results it was determined that the computer skills in solving mathematical problems of the majority of the students is very low. They have difficulties when using the TICS in their teaching-learning process. Therefore, it is advisable that teachers carry out activities in which students can use the TICS in the resolution of problem.